1963
DOI: 10.1016/s0140-6736(63)90210-1
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-Lowering Effect of Rolled Oats

Abstract: In order to compare the hypocholesterolsemic effect of some cereals and cereal products, experiments were carried out with albino rats fed the above diet with 25% of the cereal to be studied incorporated at the expense of an equal amount of wheat starch. The products under investigation were fed to rats also in combination with whole milk powder, mixed in the same ratio as used for human consumption in the Netherlands, and incorporated in the diet at a level of 25%.Each of the diets was fed ad libitum to a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
54
0
1

Year Published

1977
1977
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(55 citation statements)
references
References 1 publication
0
54
0
1
Order By: Relevance
“…In 1963 De Groot et al (1963) was the first to demonstrate experimentally that diet enriched with oat flakes decreased total serum cholesterol in healthy people. Other studies (Bartnikowska and Lange, 2000) confirmed the cholesterol lowering effects of oat products in patients with lipid metabolism disorders.…”
Section: Discussionmentioning
confidence: 99%
“…In 1963 De Groot et al (1963) was the first to demonstrate experimentally that diet enriched with oat flakes decreased total serum cholesterol in healthy people. Other studies (Bartnikowska and Lange, 2000) confirmed the cholesterol lowering effects of oat products in patients with lipid metabolism disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest has been the effects of oat soluble fibers in reducing cholesterol levels in hypercholesterolemic patients (de Groot et al 1963;Anderson et al 1984), their effects on blood sugar levels, especially insulin needs in diabetic patients (Jenkins et al 1981;Wood et al 1988), and their impact on cancer of the colon and related gastrointestinal disorders (National Research Council 1989). These beneficial effects have been primarily attributed to 1→3, 1→4-β-D-glucans (Davidson et al 1991).…”
mentioning
confidence: 99%
“…Several clinical studies starting from 1963 (DeGroot et al, 1963) were conducted to see the effect of oats on serum lipids. The most conclusive study was a meta-analysis (Ripsin et al, 1992) summarizing the oat-product literature on clinical trials of freeliving subjects up to March 1991.…”
Section: Oatmentioning
confidence: 99%